SELENIUM FRAMEWORK FOR WEB AUTOMATION TESTING: A SYSTEMATIC LITERATURE REVIEW - Hazna At Thooriqoh; Tiara Nur Annisa; Umi Laili Yuhana (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2021)
Software Testing plays a crucial role in making high-quality products. The process of manual testing is often inaccurate, unreliable, and needed more than automation testing. One of these tools, Selenium, is an open-source framework that used along with different programming languages: (python, ruby, java, PHP, c#, etc.) to automate the test cases of web applications. The purpose of this study is to summarize the research in the area of selenium automation testing to benefit the readers in designing and delivering automated software testing with Selenium. We conducted the standard systematic literature review method employing a manual search of 2408 papers, and applying a set of inclusion/exclusion criteria the final literature included 16 papers published between 2009 and 2020. The result is using Selenium as a UI for web automation, not only all of the app functionality that has been tested, But also it can be applied with added some method or other algorithms like data mining, artificial intelligence, and machine learning. Furthermore, it can be implemented for security testing. In the future research for selenium framework automation testing, the implementation should more focus on finding effective and maintainability on the application of Selenium in other methodologies and is applied with the better improvement that can be matched for web automation testing.